Unified Modelling Language (UML) Effect on the Total Cost of Ownership (TCO) for a Software Development - Ahmed Altaher (Iraqi Journal of Science, 2021)
UML (Unfiled Modeling Language), known as the standard method for object-oriented (analysis and design) modeling, includes other languages which enables it to implement a prototype of the structure and behaviors of the product. This paper attempts to explore the observations about UML role on the cost of software maintenance, and hence on the Total Cost of Ownership (TCO) of a software product. It is therefore important to investigate the benefits obtained through modeling..